2015
DOI: 10.1002/zoo.21212
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of digestive anatomy, feed intake and digestion in the Chinese pangolin (Manis pentadactyla) at Taipei zoo

Abstract: Pangolins are considered difficult to maintain in zoos, often attributed to problems in feeding management. Taipei Zoo's designation as a wildlife rescue center for Chinese pangolins (Manis pentadactyla) has resulted in long term feeding experience with development of diets that support recovery, maintenance, and reproduction, as well as experimental opportunities to further understand digestive physiology to optimize nutrition. Opportunistic dissection of 10 animals revealed details of the tongue, salivary gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
7
39
1
Order By: Relevance
“…Diets which contained a higher amount of chitin may have increased apparent organic matter digestibility due to the larger food mean retention time associated with more chitinous diets (Lin, Chang, Yang, & Dierenfeld, 2015). A similar observation made with soil addition by Chin et al (2009).…”
Section: Other Factors To Considermentioning
confidence: 53%
See 1 more Smart Citation
“…Diets which contained a higher amount of chitin may have increased apparent organic matter digestibility due to the larger food mean retention time associated with more chitinous diets (Lin, Chang, Yang, & Dierenfeld, 2015). A similar observation made with soil addition by Chin et al (2009).…”
Section: Other Factors To Considermentioning
confidence: 53%
“…In addition, perhaps the Chinese pangolins were simply fed too large of a quantity, which may have no reflection on the nutritional content of their diets. Diets which contained a higher amount of chitin may have increased apparent organic matter digestibility due to the larger food mean retention time associated with more chitinous diets (Lin, Chang, Yang, & Dierenfeld, ). A similar observation made with soil addition by Chin et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Pangolins do produce copious amounts of viscous saliva that is thought to increase the adherence of ants and termites to the tongue during feeding (Doran & Allbrook, 1973). Interestingly, anatomical description of the salivary glands of the pangolin has indicated that both the sublingual and submandibular glands are large, whereas the parotid gland is quite small (Doran & Allbrook, 1973;Lin, Chang, Yang, & Dierenfeld, 2015). The central autonomic control of the sublingual and submandibular glands arises from the superior salivatory nucleus (pVII), while that of the parotid gland arises from the inferior salivatory nucleus (pIX) (e.g., Biljani & Keswani, 2004;Chibuzo & Cummings, 1980;Rezek et al, 2008;Wang, 1943;Way, 1981).…”
Section: The Brainstem Auditory System Of the Tree Pangolinmentioning
confidence: 99%
“…In captivity, replicating the diet of free‐ranging echidnas is problematic, because of difficulties providing adequate quantities of ants and termites for food. Captive diets used for echidnas, and for other myrmecophagous species, often include some of the following: raw meat, eggs, bran, vegetable oil, wheat germ and cat or dog food mixed together with water and vitamin and mineral supplements [Jackson, ; Augee et al, ; Gull et al, ; Lin et al, ]. Generally the mixture is presented as slurry to cater for the specialized anatomy of the echidna bill.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Some captive myrmecophages, including Chinese pangolins ( Manis pentadactyla ) and giant anteaters ( Myrmecophaga tridactyla ), have been transitioned to new manufactured diets in captivity with mixed success [Gull et al, ; Lin et al, ]. The aims of the study were to: (1) transition captive short‐beaked echidnas over to a new insectivore diet; (2) determine digestibility and palatability of the new manufactured diet; (3) test the efficacy of using fiber instead of soil in the diet.…”
Section: Statement Of the Problemmentioning
confidence: 99%